Analysis of the Validated Transition Failure Criterion Model for Slope Stability in the Final Wall of a High-Sulphidation Epithermal Open-Pit Mine - M Alfiza Farhan; Akbar Aprian (EKSPLORIUM, 2025)
Open-pit slope stability in hydrothermally altered and clay-rich settings remains a critical challenge in geotechnical design. Conventional criteria, such as the Mohr–Coulomb and Generalized Hoek–Brown (GHB) models, often fail to accurately represent the intermediate soil–rock behavior of transition materials. This study applies and validates the Validated Transition (VT) criterion, a refinement of the GHB model, within a Finite Element Method (FEM) framework to evaluate slope stability in the final wall of a high-sulphidation epithermal open-pit mine. Transition rock properties were derived from Point Load Index (PLI) correlations with Uniaxial Compressive Strength (UCS), ensuring a representative characterization of hydrothermal clay-altered lithologies. Numerical simulations were performed to compare slope responses under the VT, GHB, and Mohr–Coulomb (MC) formulations. Results show that the VT model provides the highest consistency with radar-monitored displacements, achieving up to 93% agreement in low- to medium-strength rock masses, while GHB and MC produced lower correlations. This demonstrates that the VT model more effectively captures the deformation behavior of transitional rock masses, improving predictive reliability over conventional approaches. Beyond the studied case, the VT–FEM approach establishes a methodological framework that can be extended to other open-pit mines with similar geomechanical conditions. The findings emphasize the importance of transition material-specific failure criteria, supporting optimized pit design and cost-effective wall management aligned with safety standards.